PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP LOYALITAS KONSUMEN KARTU PRA BAYAR IM3 ( Studi Kasus Pada Mahasiswa STIE Assholeh di Pemalang ) (Students' Journal of Economic and Management, 2013)
Consumer loyalty is an attitude towards a brand like that presented in the purchase of the brand's consistent all the time. Loyalty is a measure of the relationship of consumers to a brand. A consumer who is very loyal to a brand will not easily move their purchases to other brands, no matter what happens with the brand. Many factors can affect customer loyalty, such as quality of service and price. The selected object is the product of a cellular card IM3 Indosat. The purpose of this study was to analyze the effect of service quality and price on consumer loyalty IM3 prepaid card. The population in this study was student of STIE Assholeh, Jl. No Sindoro. 19, Pemalang IM3 prepaid card users. The sample in this study was 100 students. Sampling technique using accidental sampling (sampling coincidence). Data collection techniques used were primary. The analysis technique used is multiple regression. The results showed that: (1). Impact of service quality on consumer loyalty. (2). Price effect on customer loyalty. (3). Quality of service and price effect on customer loyalty. Keywords: Quality of Service, Price, Consumer Loyalty